Bone mineral density in women using depot medroxyprogesterone acetate (DMPA) for at least 2 years compared to a control group: A cross sectional study - Saipin Pongsatha (2018)
Objective: To compare the effect of long-term use of depot medroxyprogesterone acetate (DMPA) on bone mineral density (BMD) in Thai women compared to the control. Material and Method: A cross sectional study was conducted on Thai women of reproductive age who used DMPA (50 subjects) for contraception for at least 2 years and non-hormonal users (50 subjects). BMD was measured at the lumbar spine, femur and distal radius, and ulna. Results: There was significantly lower BMD at the lumbar spines in the DMPA group but there was no significant difference in BMD between groups at the femur, distal radius, and ulna. Conclusion: Long-term use of DMPA has a negative impact on lumbar spine BMD.